Effects of pressure on GaN growth in a specific warm-wall MOCVD reactor. Issue 8 (31st January 2023) - Niu, Huidan; Yao, Weizhen; Yang, Shaoyan; Liu, Xianglin; Chen, Qingqing; Wang, Lianshan; Wang, Huanhua; Wang, Zhanguo
Abstract : A horizontal warm-wall MOCVD reactor with a Mo reflector screen stabilizes the temperature field and facilitates TMG decomposition. Abstract : A horizontal warm-wall metal–organic chemical vapor deposition (MOCVD) reactor was designed for growing high-quality gallium nitride (GaN) films. The reactor features a Mo reflector screen above the ceiling stabilizing the temperature field, which can realize a ceiling temperature of 790 °C and a temperature gradient within 6 °C mm −1 above the substrate. The pressure-dependent phenomenon of the reactor is explored from 50 to 150 Torr for studying the growth rate and thickness uniformity of GaN films grown on a 4 in. c -plane sapphire. The growth rate of the GaN sample at 150 Torr is slowed, because higher pressure leads to parasitic reactions consuming a lot of precursors. High crystal quality and smooth surface morphology of GaN films are achieved simultaneously using the warm-wall MOCVD. The photoluminescence (PL) spectra have few yellow luminescence (YL) bands derived from gallium vacancies, carbon impurities and related point defects, due to the conducive trimethylgallium (TMG) decomposition in the warm-wall MOCVD reactor. Moreover, the chemical reaction mechanism has been studied for the warm-wall MOCVD system, where promoting the pyrolysis reaction in the gas phase is helpful to reduce the concentration of point defects in GaN films. This work provides a practical case for epitaxial nitride materials and plays an important role in promoting the development of MOCVD equipment.